Study of Risk Factors for Total Attack Rate and Transmission Dynamics of Norovirus Outbreaks, Jiangsu Province, China, From 2012 to 2018 - Ai, Jing; Zhu, Yuanzhao; Fu, Jianguang; Cheng, Xiaoqing; Zhang, Xuefeng; Ji, Hong; Liu, Wendong; Rui, Jia; Xu, Jingwen; Yang, Tianlong; Wang, Yao; Liu, Xingchun; et al. (Frontiers in Medicine, 2022)
Objective: To describe the epidemiological characteristics of norovirus outbreaks in Jiangsu Province, utilize the total attack rate (TAR) and transmissibility (Runc) as the measurement indicators of the outbreak, and a statistical difference in risk factors associated with TAR and transmissibility was compared. Ultimately, this study aimed to provide scientific suggestions to develop the most appropriate prevention and control measures. Method: We collected epidemiological data from investigation reports of all norovirus outbreaks in Jiangsu Province from 2012 to 2018 and performed epidemiological descriptions, sequenced the genes of the positive specimens collected that were eligible for sequencing, created a database and calculated the TAR, constructed SEIAR and SEIARW transmission dynamic models to calculate Runc, and performed statistical analyses of risk factors associated with the TAR and Runc. Results: We collected a total of 206 reported outbreaks, of which 145 could be used to calculate transmissibility. The mean TAR in was 2.6% and the mean Runc was 12.2. The epidemiological characteristics of norovirus outbreaks showed an overall increasing trend in the number of norovirus outbreaks from 2012 to 2018; more outbreaks in southern Jiangsu than northern Jiangsu; more outbreaks in urban areas than in rural areas; outbreaks occurred mostly in autumn and winter. Most of the sites where outbreaks occurred were schools, especially primary schools. Interpersonal transmission accounted for the majority. Analysis of the genotypes of noroviruses revealed that the major genotypes of the viruses changed every three years, with the GII.2 [P16] type of norovirus dominating from 2016 to 2018. Statistical analysis of TAR associated with risk factors found statistical differences in all risk factors, including time (year, month, season), location (geographic location, type of settlement, type of premises), population (total number of susceptible people at the outbreak site), transmission route, and genotype (P < 0.05). Statistical analysis of transmissibility associated with risk factors revealed that only transmissibility was statistically different between sites. Conclusions: The number of norovirus outbreaks in Jiangsu Province continues to increase during the follow-up period. Our findings highlight the impact of different factors on norovirus outbreaks and identify the key points of prevention and control in Jiangsu Province.